Integral model of oral health care in Pachacútec, Callao - Madrid Chumacero, Marco Tulio (2011)
The principal aim of the model was to raise the quality of dental care through comprehensive measures for promotion, prevention and healing in the community. Specific aims were to increase the healthy population through promotion of health and reduce the morbidity of oral diseases by preventive actions and first class welfare care. A cross-sectional descriptive study. Revised Health Situation Analysis (HSA) of the Microgrid 03, the modified tab WHO oral health assessment is applied and oral exams to 100 families and 75 children of School N.° 5130. The leading causes of death were hypertension, diabetes mellitus and pneumonia. The leading causes of morbidity were acute respiratory infections, intestinal infectious diseases and diseases of the oral cavity. Tooth decay affects 80 % group of 6 to 15 years, followed by 57.34 % of malocclusion and periodontal disease with 20 %. Regarding oral hygiene most children have regular status (56 %), followed by poor hygiene (25.3 %) and only 18.7 % with good oral hygiene. We conclude that the student population shows high prevalence of dental caries, malocclusion and few maintain good oral hygiene, which reveals the need for integral treatment by the proposed model and the agreement between the San Marcos Faculty of Dentistry and Educational Institutions of EUS Ventanilla, Callao.